Interactions of Transition Metal Dichalcogenide Nanosheets With Mucin: Quartz Crystal Microbalance With Dissipation, Surface Plasmon Resonance, and Spectroscopic Probing - Liu, Boshi; Yu, Tao; Huang, Renliang; Su, Rongxin; Qi, Wei; He, Zhimin (Frontiers in Chemistry, 2019)
Ultrathin 2-dimensional transition metal dichalcogenides (TMDs) have become a class of high-potential materials in biomedicine due to their intriguing properties. They have been applied to solve biomedical challenges, such as biosensing, bioimaging, drug delivery and cancer therapy. However, studies of the interactions between these materials and biomolecules are insufficient. Mucous tissue serves as a barrier to foreign hazardous substances and a gel layer for substance exchange. The main organic matter of mucous tissue is mucin, so it was selected as a model biomolecule to study its interactions with six different TMD nanosheets (NSs), including single-layered (SL), few-layered (FL), and small few-layered (SFL) MoS2 and WS2 NSs, using quartz crystal microbalance with a dissipation monitor (QCM-D) and surface plasmon resonance (SPR). Additionally, UV absorption, fluorescence, and circular dichroism (CD) spectroscopy were applied to investigate the mechanism of the interactions and to study the conformational change of mucin. We found that the TMD NSs could adsorb on the mucin layer and affect its viscoelasticity. The results indicated that the SL WS2 NSs exhibited the highest initial absorption rate and the maximum absorption amount, while the SL MoS2 NSs exhibited the highest initial desorption rate. During the adsorption, the viscoelasticity variations of the mucin layer caused by the WS2 nanosheets were weaker than those caused by the MoS2 nanosheets. Furthermore, the conformational changes of mucin caused by the SL MoS2, SL WS2 and SFL MoS2 NSs were higher than those resulting from other TMD NSs. These findings provide important information on the interactions between TMD NSs and mucin and provide useful insights into the interfacial behavior of TMD NSs before they enter tissues.